Analisis Lingkungan Kerja Terhadap Kinerja Program Penanggulangan Tuberkulosis - Elok Alfiyah; Yunita Yunita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Work environment is the most important part in improving the performance of employees in an organization. a good work environment is closely related to effective performance. Objective: Analyze the work environment on the performance of the tuberculosis control program Methods: This type of research is a study that uses an observational approach with a cross-sectional research design and a sampling technique using probability sampling. The respondents used were the executors of the tuberculosis control program at the Surabaya City Health Center as many as 28 teams. Results: The results of this study provide information that there is an influence between the work environment and the performance of the tuberculosis control program. Based on the results of this study, it can be explained that the work environment also has an important role to be able to help the tuberculosis control program management team to achieve better performance targets. Conclusion: The work environment affects the performance of tuberculosis control program officers at the Surabaya City Health Center.